'It's more than just performing well in your sport. It's also about being healthy physically, mentally, emotionally, and spiritually': Indigenous women athletes' meanings and experiences of flourishing in sport. Issue 1 (1st January 2019) - Ferguson, Leah; Epp, Gillian B.; Wuttunee, Kellie; Dunn, Matthew; McHugh, Tara-Leigh; Humbert, M. Louise
Abstract: Sport participation can foster a wide range of positive psychosocial outcomes for women, including feeling empowered and self-sufficient, as well as gaining confidence, determination and self-respect. These well-documented potential benefits stem from research with non-Indigenous athletes, yet there is little published research to support an in-depth understanding of Indigenous women's unique sport experiences. Such understandings are necessary for meaningful sport programme implementation, health optimisation and sport policy development. The purpose of this study was to explore the phenomenon of flourishing in sport for Indigenous women athletes. Two Indigenous community sport advisors were instrumentally involved throughout the study. Sixteen Indigenous women athletes ( M age  = 21.5 years; 10 First Nations, 6 Métis) from urban, rural and remote communities in a mid-Western Canadian province participated in sharing circles and symbol-based reflection to share their meanings and experiences of flourishing in sport. A four-step phenomenological structural analysis was used to analyse transcribed data. Four essential components and one facilitating component emerged as the general structure of flourishing in sport: (1) Multidimensional Community Support (having support from and for one's family, home and sporting community); (2) Personal Accomplishments (setting and attaining individually tailored goals); (3) Persistent Growth (constant self-betterment); (4) Wholistic Athletic Excellence (excelling as a whole; physically, intellectually, spiritually and emotionally); and, (5) Humble Recognition (being acknowledged; a facilitating component). Nurturing Indigenous women athletes' flourishing in sport requires athlete-specific attention and collaborative community engagement.